Katekisasi Sebagai Media Pemuridan di Era 5.0 - Jackgues Al Idrus, Jack; Martin Aramana, Martin; Afri Aui, Afri; Moses Walukow, Moses; Yosua Tandaju, Yosua; Tesalonika Kambey, Tesa (PARADOSI: Jurnal Teologi Praktika, 2025)
The rapid evolution of technology in the Industry 5.0 era has reshaped many aspects of daily life, including how the Christian faith is taught and nurtured. Digital platforms, social media, and audiovisual content have become central to communication and learning processes. In response, catechesis must undergo a meaningful transformation to maintain its relevance in a digitally immersed culture. This paper investigates how technology can be integrated into catechetical instruction, how social media can function as a space for discipleship, and what innovative strategies are necessary in this new digital landscape. Using a qualitative approach rooted in literature-based research, this study synthesizes insights from various digital sources, including Google Scholar and online publications. The analysis reveals that digital catechesis offers a compelling and context-sensitive approach for transmitting Christian teachings to the present generation in an engaging and accessible manner.   Kemajuan teknologi pada era Industri 5.0 telah membawa dampak besar terhadap berbagai aspek kehidupan, termasuk dalam pembentukan dan pengajaran iman Kristen. Media digital, jejaring sosial, dan konten audio-visual kini menjadi alat utama dalam menyampaikan informasi dan nilai-nilai. Dalam konteks ini, katekisasi dituntut untuk berinovasi agar tetap relevan dengan kebutuhan zaman. Artikel ini mengulas bagaimana teknologi dapat diintegrasikan ke dalam materi katekisasi, bagaimana media sosial dapat dimanfaatkan sebagai ruang pemuridan, serta strategi-strategi kreatif yang mampu menjawab tantangan era digital. Penelitian ini memakai metode kualitatif berbasis kajian literatur, dengan merujuk pada berbagai sumber daring seperti Google Scholar dan pustaka digital lainnya. Hasil kajian menunjukkan bahwa pendekatan katekisasi berbasis digital mampu menghadirkan pembelajaran iman Kristen yang lebih kontekstual, komunikatif, dan menjangkau generasi masa kini secara efektif.